Loop-mediated isothermal amplification for the detection of infectious spleen and kidney necrosis virus - Mohamed Din, Mohamed Shariff; Subramanian, Kuttichantran; Bejo, Mohd Hair; Omar, Abdul Rahman; Ong, Bee Lee (2013)
The present invention provides a loop-mediated isothermal amplification (LAMP) method for the detection of infectious spleen and kidney necrosis virus (ISKNV) infection by amplifying a portion of ISKNV major capsid protein (MCP) gene using isothermal amplification and detecting the amplified product by acridine orange. Newly designed primers for use with this specific method are provided as well.The LAMP assay of the invention is specific towards ISKNV and there was no cross-amplification with other pathogens including the RSIV.